Guidance on the characterisation of microorganisms used as feed additives or as production organisms. (28th March 2018) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract : Draft Endorsed by the FEEDAP Panel * 18 May 2017 Submitted for public consultation 15 June 2017 End of public consultation 15 September 2017 Adopted by the FEEDAP Panel 21 February 2018 Implementation date 1 September 2018 : * Sections 3.1 and 3.2 were also endorsed by the EFSA Panel on Genetically Modified Organisms (GMO), EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF) and EFSA Panel on Food Additives and Nutrient Sources Added to Food (ANS) on 18 May (GMO) and 7 June (CEF and ANS) 2017. Abstract: This guidance document is intended to assist the applicant in the preparation and the presentation of an application, as foreseen in Article 7.6 of Regulation (EC) No 1831/2003, for the authorisation of additives for use in animal nutrition. It specifically covers the characterisation of microorganisms used as feed additives or as production organisms. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2018.EN-1389/full